Agabus (Acatodes) puetzi sp. n., a new species of the confinis-group from the Qinghai-Tibet Plateau (Coleoptera, Dytiscidae, Agabini) - Fery, Hans (Zootaxa, 2011)
Agabus puetzi sp. n. is described from the eastern part of the Qinghai-Tibet Plateau (Sichuan). It is a very distinctive species, males of which can be identified easily even in the field because the inner outline of the protibiae is distinctly curved, a feature which is unknown or considerably less prominent in any other Agabus Leach, 1817. The new species undoubtedly belongs to the subgenus Acatodes Thomson, 1859, although males lack the preapical spine of the median lobe, a character which is also seen in the Nearctic Agabus audeni Wallis, 1933, and the Holarctic Agabus inexspectatus Nilsson, 1990. Due to an unusual combination of external characters (e.g., double reticulation, shape of tibiae and of proand metasternal processes) it is not easy to assign the species to one of the known species groups of the subgenus. It seems likely, however, that it belongs to the confinis-group because several other characters are shared with most members of this group. A few features suggest a closer relationship to Agabus thomsoni (J. Sahlberg, 1871) and Agabus zetterstedti Thomson, 1856. The new species raises the number of members of the confinis-group to 36, seven of which occur in China. A list of all Afrotropical and Palearctic members of this group is given and their median lobes are figured in lateral view. The lectotype of Agabus turcmenus Guignot, 1957 is designated, and its habitus and aedeagus are illustrated for the first time. Some notes on the distribution and external morphology of A. inexspectatus are included.